Accuracy of pre-hospital HEART score risk classification using point of care versus high sensitive troponin in suspected NSTE-ACS - van Dongen, Dominique N.; Fokkert, Marion J.; Tolsma, Rudolf T.; van der Sluis, Aize; Slingerland, Robbert J.; Badings, Erik A.; van 't Hof, Arnoud W.J.; Ottervanger, Jan Paul (The American journal of emergency medicine, 2020)
Pre-hospital risk classification by the HEART score is performed with point of care troponin assessment. However, point of care troponin is less sensitive than high sensitive troponin measurement which is used in the hospital setting. In this study we compared pre-hospital HEART-score risk classification using point of care troponin versus high sensitive troponin. In 689 consecutive patients with suspected NSTE-ACS, point of care troponin and laboratory high-sensitive troponin were measured in pre-hospital derived blood. For every patient the HEART score with both point of care troponin (HEART-POC) and high sensitive troponin (HEART-hsTnT) was determined. Endpoint was MACE within 45 days. Mean age was 64 (SD ± 14), 163 (24%) patients were considered low-risk by HEART-hsTnT and 170 (25%) by HEART-POC. MACE was observed in 17%. Although high sensitive versus POC troponin scoring was different in 130 (19%) of patients, in 678 (98%) patients risk classification in low versus intermediate-high risk was similar. The predictive values of HEART-POC versus HEART-HsTnT was similar (AUC 0.75 versus 0.76, p = 0.241). Although high sensitive versus POC troponin scoring was dissimilar in one fifth of patients, this resulted in different patient risk classification in only 2 percent of patients. Therefore POC troponin measurement suffices for pre-hospital risk stratification of suspected NSTE-ACS.